A geostationary orbit microwave multi-channel radiometer - Zhou, Weilai; Lv, Rongchuan; Li, Hao; Li, Yinan; Dou, Haofeng; He, Zheng; Shen, Shangyu; Gao, Wenyu; Ren, He; Zhang, Long; Jin, Liang (Frontiers in Physics, 2023)
The geostationary orbit microwave multi-channel radiometer has the advantages of high real-time performance and large coverage, which plays an important role in typhoon, strong precipitation detection, and medium-to-short-term meteorological/oceanic forecasting. However, due to the difficulty in engineering development of the payload, its application on-orbit has not yet been achieved at present. To satisfy the requirements of fine and quantitative application of satellite observation data, a geostationary orbit microwave multi-channel radiometer with a 10-m-caliber is developed, in which the spatial resolution at horizontal polarization is better than 24 km at 54 GHz. In geostationary orbit microwave multi-channel radiometer, a quasi-optical feed network covering nearly 28 frequency octave bands and ranging from 23.8 to 664 GHz is proposed to solve the technical problem of multi-frequency sharing in the system. Meanwhile, a high-precision reflector preparation method and a high-precision unfolding scheme are proposed, which are considered as a solution for the large-diameter reflector with a high maintaining surface accuracy. A high-precision antenna prototype with 0.54-m is developed, and the tests are performed to verify the key technologies, such as the preparation of high-precision grating reflectors at the micron level, high surface accuracy detection, and sub-millimeter wave antenna electrical performance testing. The results indicate that measured main beam efficiency of the 664 GHz antenna is better than 95.5%. In addition, the system sensitivity is greater than 1.5 K, and the calibration accuracy is better than 1.8 K, according to the results of an analysis of the multi-channel radiometer’s essential parameters and calibration errors.